2006
DOI: 10.1021/ac051651m
|View full text |Cite
|
Sign up to set email alerts
|

Cell Interaction Microarray for Blood Phenotyping

Abstract: Microarrays promise great advances in areas of diagnostic testing where there is a need to perform multiple assays in parallel. In the short term, protein microarrays have a greater potential to impact diagnostics than DNA arrays due to their potential for direct sample measurements. Here, we report an antibody microarray technique for selectively recognizing glycan and peptide motifs on the surface of red blood cells. We present results demonstrating the optimization and efficacy of the microarray approach as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…8,[50][51][52] As for example, Campbel et al evaluated several intact IgG and IgM antibodies as probes for membrane protein profiling recently and found that the choice of antibody was not obvious, since many antibodies with similar solution reactivity differed in performance on a microarray surface. 29 In contrast, we have repeatedly demonstrated the specificity and on-chip functionality of our microarray-adapted scFvs, even when targeting low-abundance protein analytes in directly labeled complex proteomes, such as human serum and plasma. 1,[32][33][34][35]49 In accordance, the stringently selected scFvs used in this study, targeting cell surface membrane proteins and cell surface associated carbohydrates, was also found to display adequate specificity (e.g., Figures 1, 4, and 7).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…8,[50][51][52] As for example, Campbel et al evaluated several intact IgG and IgM antibodies as probes for membrane protein profiling recently and found that the choice of antibody was not obvious, since many antibodies with similar solution reactivity differed in performance on a microarray surface. 29 In contrast, we have repeatedly demonstrated the specificity and on-chip functionality of our microarray-adapted scFvs, even when targeting low-abundance protein analytes in directly labeled complex proteomes, such as human serum and plasma. 1,[32][33][34][35]49 In accordance, the stringently selected scFvs used in this study, targeting cell surface membrane proteins and cell surface associated carbohydrates, was also found to display adequate specificity (e.g., Figures 1, 4, and 7).…”
Section: Discussionmentioning
confidence: 91%
“…[23][24][25][26][27][28][29] In the case of fluorescent-based readout, the cells were detected by either (i) direct or indirect labeling of the cells [24][25][26][27][28] or (ii) a label-free manner taking advantage of the cells' autofluorescent properties. 29 Here, we expanded the range of competitive fluorescent-based setups by interfacing black polymer Maxisorb slides with a confocal scanner and ZeptoMARK glass slides with a PWG scanner. Of note, the PWG technology has previously been shown to provide excellent sensitivity in the case of antibody/protein microarrays targeting water-soluble protein analytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to generate pre-determined cell patterns on the substrate surface is a key step for studying tissue formation and cellular function in vitro, which are usually regulated by diverse biological factors including cell-cell communication, cell-matrix interactions, and soluble factors (Attucks and Katula 2001;Campbell et al 2006;Heasley 2001;Javazon et al 2001;Quehenberger 2005). Patterning cells on a specific area with defined shapes are also necessary for investigating the function of cell interaction (Campbell et al 2006;Rosenthal et al 2007) and the migration of cell in substrate (Nakanishi et al 2007;Onuki-Nagasaki et al 2008).…”
Section: Introductionmentioning
confidence: 99%